Legal protection for people with mental disorders (PWMD) handling related approval of medical action - SUTARNO, H. (Utopía y Praxis Latinoamericana, 2019)
ABSTRACT Medical malpractice is the unfulfilled rights of patients due to poor communication or information. The doctor-patient relationship during therapeutic transactions, such as in the case of an agreement, needs to meet the conditions stated in Article 1320 of the Civil Code. Therefore, their rights and obligations need to be fulfilled and carried out in good faith to achieve a common good. Patient-oriented utilitarianism is an example of an ethic situation, because the decision-makers consider the consequences of their actions, while a clinical person needs to analyze decisions in a broader perspective. RESUMEN La negligencia médica es el incumplimiento de los derechos de los pacientes debido a la falta de comunicación o información. La relación médico-paciente durante las transacciones terapéuticas, como en el caso de un acuerdo, debe cumplir con las condiciones establecidas en el Artículo 1320 del Código Civil. Por lo tanto, sus derechos y obligaciones deben cumplirse y llevarse a cabo de buena fe para lograr un bien común. El utilitarismo orientado al paciente es un ejemplo de una situación ética, porque los tomadores de decisiones consideran las consecuencias de sus acciones, mientras que una persona clínica necesita analizar las decisiones en una perspectiva más amplia.